Characterization of Composite Edible Film of Winged Bean Seeds Protein and Tapioca - C Dewi Poeloengasih; Djagal W Marseno (Jurnal Teknologi dan Industri Pangan, 2003)
The advantageous winged bean seeds and tapioca as edible film ingredients are due to its relative abundance, inexpensive, biodegradable and their renewable nature. Research objectives were to isolate protein of winged bean (Psophocarpus tetragonolobus L. (DC.)) seeds and to characterize physical, mechanical and barrier properties of edible film made from protein fraction of winged bean seeds, tapioca and palmitic acid. The first group of edible film was prepared using 1% (w/v) of tapioca, 1 – 2,5% (w/v) of protein fraction of winged bean seeds and 1% (w/v) of sorbitol. Second group of edible film was prepared using 1% (w/v) of tapioca, 2,5% of protein fraction of winged bean seeds, 1% (w/v) of sorbitol and 0-8% (w/w polymer) of palmitic acid. Proximate analysis of protein fraction of winged bean seeds showed that protein, lipid, ash and water content were 57,88%, 29,39%, 1,66% and 7,10%, respectively. Increasing the concentration of protein fraction of winged bean seeds decreased water vapor transmission rate and elongation, and increased thickness and tensile strength. Increasing the concentration of palmitic acid decreased water vapor transmission rate and tensile strength, and increased elongation. Utilization of 1% (w/v) of tapioca, 2,5% (w/v) of protein fraction of winged bean seeds, 1% (w/v) of sorbitol and 8% (w/w polymer) of palmitic acid to wrap the fresh-cut apple has significant effect on reducing of weight loss and browning during storage. Key words : Winged bean seeds, protein, tapioca, composite edible film.